Neurologic manifestations of legionnaire's disease in the absence of pulmonary symptoms - Leong, Wan Yi; Abdul Rashid, Anna Misyail; Baharin, Janudin; Wan Sulaiman, Wan Aliaa; Inche Mat, Liyana Najwa; Basri, Hamidon (Brunei International Medical Journal, 2022)
Legionnaires' disease, also known as legionellosis is caused by bacteria legionella. It commonly presents with respiratory symptoms and extrapulmonary legionella disease is rare. Here we re-port a rare case of Legionnaire’s disease with meningoencephalitis in a patient without pulmonary involvement. Imaging studies and cerebrospinal fluid analysis suggested meningoencephalitis. He was subsequently diagnosed with Legionella infection and was discharged well without any neuro-logical deficit after antibiotic therapy. This condition should be considered in the differential diag-nosis of meningoencephalitis